DETERMINATION OF URANIUM CONCENTRATION IN TEETH MALE SAMPLES USING FISSION TRACKS IN CR-39 FROM DIFFERENT COUNTRIES - Tawfiq, Nada F; Hummadi, Sallama S (Al-Nahrain Journal of Science, 2010)
The aim of this project is to measure the uranium concentration in teeth male samples collected from different nationalities.The uranium concentration in teeth samples were measured by using CR-39 track detector. The nuclear reaction is used as a source of nuclear fission fragments is (n, f) obtained by the bombardment of U-235 with thermal neutrons with flux (5000 n cm -2 s -1) from (Am-Be) neutronsource. The concentration values were calculated by a comparison with standard samples which prepared. The obtained results show that the concentration is ranging from (0.72 0.1ppm) in Egypt to (0.24 0.03ppm) in Pilipino for male, the uranium concentration was the highest in Egypt for male.